2002
DOI: 10.1038/sj/cdd/4400936
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-induced endothelin B receptor-mediated smooth muscle cell apoptosis is matrix-dependent

Abstract: To maintain normal blood flow, pressure overload in both arteries andveinsrequiresastructuraladaptation ofthevessel wall (remodelling) that involves smooth muscle cell (SMC) hypertrophy and/or hyperplasia. Due to its potent vasoconstrictor and growth-promoting effects, endothelin-1 (ET-1) is a likely candidate to initiate and/or promote remodelling in blood vessels exposed to a chronic increase in blood pressure. To test this hypothesis, isolated segments of the rabbit carotid artery and jugular vein were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…A changed ratio of ET‐receptor subtypes results in a modified signal transduction, because ETA‐ and ETB‐receptors couple in part to different Gα proteins. For example in smooth muscle cells, a shift towards the ETB‐receptor causes a deformation of these cells [60], whereas in human myocardial fibroblasts a shift towards the ETA‐receptor profoundly interferes with cellular Ca 2+ regulation [57]. Moreover, it is described that the ETA‐receptor regulates proliferation by pro‐ and antimitogenic actions [24,61].…”
Section: Discussionmentioning
confidence: 99%
“…A changed ratio of ET‐receptor subtypes results in a modified signal transduction, because ETA‐ and ETB‐receptors couple in part to different Gα proteins. For example in smooth muscle cells, a shift towards the ETB‐receptor causes a deformation of these cells [60], whereas in human myocardial fibroblasts a shift towards the ETA‐receptor profoundly interferes with cellular Ca 2+ regulation [57]. Moreover, it is described that the ETA‐receptor regulates proliferation by pro‐ and antimitogenic actions [24,61].…”
Section: Discussionmentioning
confidence: 99%
“…Because endothelin ET B activation mediates opposite effects depending of the endothelial or muscular location of the receptor, the sum of these effects could have masked the effect of the activation of each of them individually. However, other studies describe the presence of endothelin ET B receptors functionally active in the rabbit carotid artery, and their possible role in several pathophysiological conditions (Lauth et al, 2000;Cattaruzza et al, 2002). In vivo studies have demonstrated that endothelin-1 contributes to regulation of the vascular tone of human resistance vessels by stimulating NO activity, and this effect is mediated through endothelial endothelin ET B receptors (Cardillo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the mechanical stress results in an increase of endothelin receptor expression in VSMCs and that exposure of these cells to endothelin will induce apoptosis via an endothelin receptor dependent mechanism [217,218]. This mechanism is sensitive to ECM interactions as it is observed in intact vessels in VSMCs cultured on fibronectin coated plates [217].…”
Section: Mechanical Stress Induced Apoptosismentioning
confidence: 99%